2007
DOI: 10.1111/j.1360-0443.2006.01694.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between genetic and environmental influences on initiation and progression of substance use

Abstract: Aims To examine the genetic and environmental contributions to the initiation of use and progression to more serious use of alcohol, cigarettes and marijuana during adolescence, and to examine the relationship between initiation and progression of substance use. Design The study used a twin-based design and a new theoretical model, the causal-common-contingent (CCC) model. This allows modelling of the relationship between initiation of use and progression to heavier use as a two-stage model and the examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 38 publications
6
109
2
1
Order By: Relevance
“…Previous research, however, has suggested that there may be qualitatively different risk factors for initiation versus progression of substance use, particularly for alcohol (Fowler et al 2007a;Heath et al 1991). Therefore, our results do not characterize etiological processes that are specific to initiation alone.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous research, however, has suggested that there may be qualitatively different risk factors for initiation versus progression of substance use, particularly for alcohol (Fowler et al 2007a;Heath et al 1991). Therefore, our results do not characterize etiological processes that are specific to initiation alone.…”
Section: Discussioncontrasting
confidence: 63%
“…An increase from early to later stage transitions in the overlap of variance in genetic risk for ND and AD with variance in alcohol and cannabis use would also explain this finding. Evidence for changes in the source of genetic contributions to smoking outcomes across stages (i.e., heritability of smoking initiation is not perfectly correlated with heritability for progression to heavier use [Fowler et al, 2006] or ND [Kendler et al, 1999;Maes et al, 2004]) lends support to this interpretation of the results.…”
Section: Cross-stage Predictors Of Transitionsmentioning
confidence: 86%
“…3 Behavioral genetic studies with twin designs have shown a significant genetic component not only in alcohol dependence (explained variance 58% 4 ), but also in regular alcohol use (43% 5 ) and alcohol-related problems (38.5% 6 ). In addition, a genetic component of approximately 30% has also been identified for initiation of drinking 7,8 (see for an overview Poelen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a developmental period in which complex environmental influences within and outside the family codetermine the initiation and use of alcohol. 7,8 In other words, certain genetic polymorphisms may increase the likelihood that a person will develop alcohol dependence or will start using alcohol very early, but the actual manifestation of the disorder or habit might depend on environmental factors, 24,25 a so-called gene-environment (G Â E) interaction.…”
Section: Introductionmentioning
confidence: 99%